Review of Oil Cooling Methods for Large Transformer Coils in the Transmission Grid - Aymen Abdul Kareem, HassanainGh. Hameed, Zaid M. Al-Dulaimi (Design Engineering, 2021)
Large oil-cooled transformers in power transmission networks have become a need for the whole world because they have two functions: the first is to raise the electric power voltage, and the second is commonly used to reduce the voltage. This is the rise and down of voltage for the transformers and the loads on them, especially in the hot climate season. Their temperature rises, so it needs coolers to reduce high temperatures to keep the input coil (windings) isolated from breakdown or explosion. The global challenge was finding a way to cool these transformers, so the experiments were experimental and numerical. Among these experiments, the best non-conductive oils were used. They can reduce the temperature of the internal parts of the transformers. Among the methods of oil cooling is either heat transfer by natural convection(AN) or forced convection(AF), so in this study, its will try to look at the modern method of reducing the temperature of the oil, taking into account several aspects, including economic, environmental, local and other important aspects.